MINIATURE OF ART EAST SCHOOLS IN ART HELD PLACE - Jabbarov Azizbek Jabborovich (Journals Park Publishing, 2024)
Miniaty ura art unique the field smallpox not but of artists difficult work the fruit being sprout came out medium centuries of culture elegant is a flower. In miniatures of our ancestor’s high culture reflection reached they are all in times the audience attention to himself attraction reached the past artists created this a miracle pictures until now own charm save because of the rest, it also fascinated our contemporaries reached is coming
Keywords: Miniature, Revival era, Arabia, India, Iran, Turkish, Syria, Iraq, Egypt, Dioscord , Fannakalogia , Gujarat , Mongol , Isfahan , Fatih album , Khamsa , Azerbaijan, Afghanistan.